Variable effects of biochar and P solubilizing microbes on crop productivity in different soil conditions. Issue 2 (7th February 2016) - Deb, Debal; Kloft, Marius; Lässig, Jörg; Walsh, Stephen
ABSTRACT: An expanding body of literature informs that biochar improves soil quality and agricultural productivity. However, there are some reports of little, or even negative, effect of biochar on crop yield, depending on the type of biochar feedstock, pyrolysis process, soil nutrient status, and crop species. Biochar is known to adsorb ammonia and phosphates in soil and facilitate growth and activities of phosphorus (P) solubilizing microbes (PSM), which mobilize P for uptake by plant roots. Using slow-pyrolyzed wood biochar and PSM in different soil conditions in three countries, our experiements show that soil nutrient status is more determinant of beneficial agronomic effect of biochar than the feedstock species and the type of crop. Treatments with biochar and PSM entail significant yield increase in P-deficient soil, whereas in soils with high P content, biochar has no significant effect on crop yield, regardless of addition of PSM. Based on published empirical data as well as our own findings, we also present a mathematical model of plant uptake of bioavailable P at different soil P concentrations, which explains that biochar is ineffective to enhance PSM activity for P mobilization in phosphate-rich soil, but significantly improves crop productivity in P-deficient soil.